Population Study of Kedukang Fish (Hexanematichthys sagor) in The Waters of Percut River, Percut Sei Tuan District, Deli Serdang Regency, North Sumatera - Ade Angelia Atmanegara Sinaga; Hesti Wahyuningsih; Kaniwa Berliani (Jurnal Penelitian Pendidikan IPA, 2023)
Kedukang fish (Hexanematichthys sagor) is a consumable fish that is widely caught by fishermen and the community. Kedukang fishing is carried out every day in the Percut River, resulting in a decline in its population. This study aims to analyze the population by looking at density, sex ratio, growth pattern, gonad maturity level, gonad maturity index and fecundity of kedukang fish and analyze the relationship between physical-chemical factors of waters with population density of Kedukang fish. Samples were taken using purposive sampling method at 3 observation stations with 2 repetitions. Fish samples were taken using a net fishing gear installed at low tide and lifted at high tide. The results showed that the population density of kedukang fish in Percut River was low ranging from 0.048-0.123 ind/m2. The sex ratio kedukang fish at each observation station has an average of 1:0.5. The growth pattern of fish is allometric negative. The frequency distribution of fish length ranged from 21.5-47.9 cm. The greatest number of fish caught had a length range of 30.3-34.7 cm as many as 9 fish. The level of gonad maturity kedukang fish is dominated by TKG V. The average gonad maturity index of female kedukang fish is highest at the TPI location which is 20.729% and the highest fecundity at station II which is 4622.6. The relationship between the density of the kedukang fish population is very strong and positively correlated with DO, light intensity and nitrate. The population density of kedukang fish was strongly and negatively correlated with pH and phosphate.